Understanding the Effects of Colleague Participation and Public Cause Proximity on Employee Volunteering Intentions: The Moderating Role of Power Distance - Hou, Jundong; Qian, Ling; Zhang, Chi (Frontiers in Psychology, 2020)
Many organizations encourage their employees to participate in charitable activities as part of their corporate social responsibility strategies. As a result, there has been an increased research interest in employee volunteering behavior. However, while previous research on employee volunteering decisions has focused on both individual-level and organizational-level factors, there has been less focus on peer involvement and volunteer cause proximity. To go some way to filling this research area, this paper conducted two studies to examine the possible effects of colleague participation, colleague position and public cause proximity on employee volunteering intentions. Study 1 found that colleague participation and public cause proximity had significant effects on employee volunteering, and study 2 found that power distance played a moderating role in the relationship between colleague position and employee volunteering. This study contributes to theoretical research on employee volunteering, and provides some information to assist firms retain engaged volunteers.